(untitled) (Ciencias Veterinarias, 2024)
The purpose of this article is to discuss some relevant facts found in several clinical cases of antibiotic resistance in equines to raise awareness about the problematic, make a literature review on the topic and propose therapeutical alternatives different to the use antibiotics currently available. The fistulous tract exemplifies a chronic wound that presents itself as a subcutaneous tunnel exiting through the skin with presence of contaminated secretion. When the tract is infected with multi-resistant bacteria and there is biofilm presence, the medical treatment is, therefore, a lot more complicated, prolonged in time and expensive due to the cost of diagnostic procedures, veterinary management, medicines, and hospital boarding, which is often required. In addition, normally, the expected zootechnical use of the animal cannot be carried out until it heals, and its price is devalued due to the injury. The role of bacterial biofilms in chronic infected wounds is addressed and due to the difficulty in identifying them, it is advisable to look for specific clinical signs suggestive of the problem and apply the “Percival´s Diagnostic Algorithm” for the detection of biofilm. Treatment should be based on repeated debridement and the application of topical antimicrobial therapy without prescribing systemic antibiotics unless there are signs of generalized infection. A treatment protocol to improve the management of the injury and the use of alternative antiseptic substances to current conventional antibiotics are discussed, as well as the application of “ONE HEALTH” concepts to deal with such problem.